Does in utero Exposure to Illness Matter? The 1918 Influenza Epidemic in Taiwan as a Natural Experiment - Ming-Jen Lin; Elaine M. Liu (Institute for the Study of Labor (IZA), 2014)
This paper uses the 1918 influenza pandemic in Taiwan as a natural experiment to test whether in utero conditions affect long-run developmental outcomes. Combining several historical and current datasets, we find that cohorts in utero during the pandemic are shorter as child/teenagers, less educated, and more likely to have serious health problems, including kidney disease, circulatory, respiratory problems, and diabetes in old age, than other birth cohorts. Despite the possible positive selection on health from high infant mortality rates during this period (18 percent), our findings suggest a strong negative effect of in utero exposure to influenza.
Keywords: I12; N35; I19; 330; height; 1918 influenza; fetal origins hypothesis; education; disease; mortality